2013
DOI: 10.1074/jbc.m113.502039
|View full text |Cite
|
Sign up to set email alerts
|

Secreted Proteases Control Autolysin-mediated Biofilm Growth of Staphylococcus aureus

Abstract: Background: Esp, a secreted protease of Staphylococcus epidermidis, blocks biofilm formation of Staphylococcus aureus and its ability to colonize human nares.Results: Esp cleaves autolysin, thereby preventing the release of staphylococcal DNA as biofilm matrix.Conclusion: Secreted proteases control S. aureus biofilm development and host colonization.Significance: Methods that promote autolysin degradation may also prevent S. aureus colonization of humans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
72
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(78 citation statements)
references
References 74 publications
4
72
0
2
Order By: Relevance
“…Staphylococcus epidermidis secretes a serine protease, Esp, which inhibits S. aureus biofilm formation (56). Esp degrades S. aureus biofilms by inactivating autolysins and preventing the release of DNA that is an essential component of the biofilm extracellular matrix (57). The presence of Corynebacterium spp.…”
mentioning
confidence: 99%
“…Staphylococcus epidermidis secretes a serine protease, Esp, which inhibits S. aureus biofilm formation (56). Esp degrades S. aureus biofilms by inactivating autolysins and preventing the release of DNA that is an essential component of the biofilm extracellular matrix (57). The presence of Corynebacterium spp.…”
mentioning
confidence: 99%
“…S6) resulting in decreased biofilm formation. 17 Therefore, it is possible that the quorum sensing RNAIII-mediated synthesis of proteases may impact the production of biofilm to favor cell dissemination. 27 Besides LytM, it was previously shown that RNAIII repressed the synthesis of SA2353, encoding an amidase.…”
Section: Discussionmentioning
confidence: 99%
“…7 Remodeling of the PG in S. aureus is in part achieved by different PG hydrolases (also known as autolysins) 8,9 whose functional redundancy may explain why individually, none of them are essential. [10][11][12] The PG hydrolases have also been associated with cell division and separation, protein secretion, biofilm formation [13][14][15][16][17][18][19] and with the bacterial programmed cell death (reviewed in 20 ). Within S. aureus, expression of the autolysins is repressed by the action of the 2-component systems ArlSR 21 and LytSR, 22 and the transcriptional regulator MgrA.…”
Section: Introductionmentioning
confidence: 99%
“…The proteases encoded in the S. aureus genome are organized into four distinct operons mediating synthesis of a metalloprotease (Aur), seven serine proteases (SspA and SplA-F) (organized in two distinct operons), and two cysteine proteases (Staphopains ScpA and SspB) (Figure 1) [20,21]. The six Spl enzymes coded by splA-F do not require proteolytic activation.…”
Section: Extracellular Proteases Of S Aureusmentioning
confidence: 99%
“…Some other Staphylococcal surface proteins or cell wall associated proteins that have been implicated in surface attachment/adhesion and possibly biofilm formation include: SasX and SasC (structurally uncharacterized), FnBPs (Fibronectin binding proteins), ClfB and Protein A [5]. Extracellular DNA (eDNA), released from cells with the help of aureolysin, a S. aureus protein, contributes to the structural stability of S. aureus biofilms [5,20].…”
Section: Extracellular Matrix Composition Of S Aureus Biofilmsmentioning
confidence: 99%